Analisis Akuntabilitas dan Transparansi Pengelolaan Dana Bantuan Operasional Sekolah (BOS) pada SD Islam Cahaya Khalifah Palu - Afriani Afriani; Sugianto Sugianto; Betty Betty; Muhammad Iqbal (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
Accountable and transparent management of School Operational Assistance (BOS) funds is essential to achieving good school financial governance and improving the quality of education. This study aims to analyze the implementation of accountability and transparency in the management of BOS funds at SD Islam Cahaya Khalifah Palu. A qualitative approach with a case study design was employed. Data were collected through interviews, observations, and documentation involving the principal, BOS treasurer, teachers, and the school committee. Data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing, while data validity was ensured through source triangulation. The findings indicate that accountability has been implemented through planning based on the School Activity and Budget Plan (RKAS), implementation in accordance with technical guidelines, proper financial administration, and reporting using the ARKAS application. Transparency is reflected in the involvement of the school committee in planning, dissemination of financial information to school stakeholders, the provision of information boards, and openness to supervision by the Education Office. The study concludes that the management of BOS funds at SD Islam Cahaya Khalifah Palu reflects the principles of good governance through accountability, transparency, and compliance with applicable regulations.